The pharmacology, toxicology, and detoxification of Aconitum kusnezoffii Reichb., traditional and modern views - Kenneth Happy; Sungyu Yang; Chang Ho Kang; Youngmin Kang (Applied Biological Chemistry)
Abstract Aconitum kusnezoffii Reichb. is a medicinal plant widely used in traditional Asian medicine, especially in Korea, for its potent pharmacological effects. However, its toxic alkaloids pose significant risk, making careful processing essential to reduce its toxicity. This study reviewed the plant’s processing methods, pharmacological activities, phytochemistry, toxicology, and detoxification techniques. Data from several databases, including Google scholar, PubMed, Scopus, Web science, peer-reviewed journal articles, classic herbal medicine books, and Allied and Complementary Medicine Database (AMED) were critically retrieved, organized and analyzed. The article’s findings indicate that, various ethnic groups in Asia have utilized different techniques, involving fire, water, or a combination of both to maximize the plant’s therapeutic potential and ensure safety. To date, more than 70 alkaloids, categorized into diterpenoids, norditerpenoids, and benzylisoquinolines, have been isolated from different plant’s parts (roots, leaves, stems, and flowers). These compounds exhibit various pharmacological activities including anti-inflammatory, analgesics, anti-cancer, anti-tumor, anti-arhythmic and pain-relieving properties. Despite its therapeutic potential, A. kusenzoffii. has narrow therapeutic window, meaning even small doses can be toxic. The study explored methods for reducing toxicity and detoxifying the herb emphasizing the importance of modern technologies such as propagation techniques, Systematic Evolution of Ligands by Exponential Enrichment (SELEX)-aptamer technology, and Chinmedomics in herbal medicine development. While research on this herb is extensive, gaps remain in clinical trials and efficacy studies. Further research is recommended to evaluate the quality of medicinal materials, understanding the herb’s pharmacodynamic substances, and assess long-term toxicity and clinical efficacy. Graphical Abstract